Pengembangan Game Wazan Berbasis Android - Purnama, Sigit; Setiyawan, Adhi (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2015)
Arabic is the lenguage of Quran. Nahwu-shorof is a tools that is very important in Arabic. Unfortunately, studied Arabic, especially nahwu-shorof, for Indonesian people is not easy. Therefore, the nahwu-shorof material should be designed simply. The learning materials should be used to learn independently and suitable with the development of technology, information, and communication. This research is a Research and Development (R & D) model. The model of development used in this research is ADDIE (analysis, design, development, implementation, and Evaluation). The product specification from this research is application nahwu shorof wazan games which working on smartphone based Android. The results of validation indicated that in general the game wazan based android have good values. All aspects of assessment: the interface, level of difficulty, constancy, hyperlinks function, speed, interactivity, and sound function have a good and normal values.